PENGARUH PEMBELAJARAN PROBLEM PROJECT BASED LEARNING (PJBL) TERHADAP BERFIKIR KRITIS SISWA - LENI WATI; ISKANDAR LUBIS (ABDUSSALAM : Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
This research is motivated by the critical thinking ability of students of SMPN 5 Kepenuhan which is still relatively low, such as students still dominate the inability to provide simple explanations well related to the material. The purpose of this study is to analyze the effect of the PJBL learning model on the critical thinking ability of students of SMP Negeri 5 Kepenuhan. This research is a quantitative study with an experimental method. Data collection used a paper pencil test for critical thinking. The population of the study was grade VIII students, while the sample of the study was class VIIIA and VIIIB with the number of students in the control class of 36 people and the experimental class of 36 people. Data analysis used the t test. Based on the results of the study, it can be concluded that the effect of the PJBL learning model on the critical thinking ability of students at SMP Negeri 5 Kepenuhan is significant. Hypothetically, this research is accepted with a contribution of 28.5% which is included in the moderate category. The rest is influenced by other factors not discussed in this study.